Bilateral dorsolateral prefrontal cortex high-frequency transcranial magnetic stimulation for consciousness recovery after traumatic brain injury: a case series - Chang, Chun-Hung; Chuang, Hao-Yu; Leung, Albert; Juan, Wei-Sheng; Lee, Jia-Hau; Tsai, Hsin-Chi (Frontiers in Psychiatry, 2025)
BackgroundRepetitive transcranial magnetic stimulation (rTMS) is a nonpharmacological intervention that can facilitate consciousness recovery after acquired brain injury. However, the effectiveness of high-frequency rTMS applied bilaterally to the dorsolateral prefrontal cortex (DLPFC) and the utility of single-photon emission computed tomography (SPECT) for monitoring treatment response remain unclear.MethodsTwo patients with severe brain injury—one with primary traumatic brain injury and the other with secondary brain injury involving hypoxemic encephalopathy following trauma—received 10Hz rTMS targeting the bilateral DLPFC (Beam-F3/F4). Each session included 40 trains of 4 seconds with 11-second intertrain intervals, delivered at 100% of the resting motor threshold. Sessions were administered daily, 5 days a week, with 10 sessions per course.ResultsBoth patients exhibited clinical improvement, with Glasgow Coma Scale scores increasing from 6 to 10 and Coma Recovery Scale–Revised scores increasing from 6 to 16 after 12 courses, indicating a transition from a vegetative state to a minimally conscious state. SPECT revealed reduced hypoperfusion in the bilateral frontal lobes, decreasing from 51% to 40% in Patient A and from 33% to 30% in Patient B. These imaging findings are consistent with the observed clinical improvements.ConclusionHigh-frequency rTMS applied bilaterally to the DLPFC may promote consciousness recovery in patients with acquired brain injury, with associated perfusion improvements observed on SPECT. Although these findings are promising, additional controlled studies in larger cohorts are required for validation.